Correlation of juvenile hormone bisepoxide iii concentration with fly larval developmental ages, and model development towards time of death - Azmi, Nur Aliah Natasha (2022)
Juvenile hormone (JH) is a sesquiterpenoid hormone found exclusively in insects and arthropods. This hormone regulates various physiological function in insects such as moulting, metamorphosis, reproduction, behaviour, and caste determination. In Diptera, juvenile hormone bisepoxide III (JHB III) has been identified as the primary homologs found in the larval stages and are well known to regulate larval moulting and metamorphosis This study aimed to measure JHB III concentration patterns in three species of forensically important flies namely Chrysomya megacephala, Chrysomya rufifacies, and Musca domestica. The larval samples analysed were obtained from both laboratory colonies and from the field simulation study. Pearson correlation test was used to examine the relationship between JHB III concentration and larval developmental age. The potential application of predicting the minimum post-mortem interval (mPMI) using JHB III concentration was also explored. JHB III detection and quantification was performed using High-Performance Liquid Chromatography (HPLC). A fluctuating pattern of JHB III concentration was reported herein for Ch. megacephala and Ch. rufifacies. As for M. domestica, there was no clear pattern observed. The highest JHB III concentration was reported at 72 hours of larval development for both Ch. megacephala and M. domestica. While in Ch. rufifacies the highest concentration was at 120 hours. Correlations between larval developmental age and the JHB III concentration was reported in all three species of flies. However, the correlation was not statistically significant (p > 0.05). Based on the regression model, JHB III concentration was not a reliable predictor in estimating fly larval developmental age. In conclusion, the concentration of JHB III in fly larvae cannot be used to predict the larval age, or specifically, the mPMI; instead, the decline of the hormone at the end of larval-larval moult may be used to determine the initiation of metamorphosis.